Comparison of independent randomised reading of radiographs with direct progression scoring for assessing change in asbestos-related pulmonary and pleural lesions. - McMillan, G H (1982)
Direct scoring of progression of pleural and parenchymal lesions was compared with change assessed by independent readings to the ILO classification among 155 men from HM Dockyard, Devonport, followed-up for 10 years. For pleural calcification the two methods agreed closely, whereas direct scoring yielded relatively too little progression of small opacities and too much progression of pleural thickening. The choice of method for assessing progression should depend on objectives.